Managing public institutions of higher learning in Malaysia: An interview with Deputy Director General of The Department Of Higher Education Management. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2005)
Education, at all levels, has always been important to Malaysians. It has been the means to optimally utilize resources, i.e. natural materials and human related, towards socio-economic growth and development. It is in the pursuit of education that Malaysians, of all ages, have ventured within and abroad as temporary educational migrants. In the distant past, the Middle-east, India and England may have been the traditional destinations abroad. Modern Malaysians are jet-setters carrying on this pursuit and academic sojourns in America, Japan, Russia to name a few, however brief, have been and still are domains of the Malaysian intelligentsia.